Understanding the electrochemical reaction mechanism of VS2 nanosheets in lithium-ion cells by multiple in situ and ex situ x-ray spectroscopy. (17th September 2018) - Zhang, Liang; Sun, Dan; Wei, Qiulong; Ju, Huanxin; Feng, Jun; Zhu, Junfa; Mai, Liqiang; Cairns, Elton J; Guo, Jinghua
Abstract: Recently, 2D layered transition metal dichalcogenides (TMDs) have attracted great scientific interest in electrochemical energy storage research. Vanadium disulfide (VS2 ) as an important family member of TMDs, is a promising electrode material for lithium-ion cells because of its remarkable electrical conductivity and high Li + diffusion rate, but its electrochemical reaction mechanism is still poorly understood. Herein, we have prepared VS2 nanosheets as the electrode and systematically investigated its structural and chemical evolution during the electrochemical processes by employing both in situ and ex situ x-ray spectroscopy. The VS2 undergoes intercalation and conversion reactions in sequence during discharge and this process is found to be partially reversible during the subsequent charge. The decreased reversibility of the conversion reaction over extended cycles could be mainly responsible for the capacity fading of the VS2 electrode. In addition, the hybridization strength between S and V shows a strong dependence on the states of charge, as directly illustrated by the intensity change of the V–S hybridized states and pure V states. We have also found that the solid electrolyte interphase on the electrode surface is dynamically evolved during cycling, which may be a universal phenomenon for the conversion-based electrodes. This study is expected to be beneficial for the further development of high-performance VS2 -based electrodes.